1985
DOI: 10.1111/j.1600-0722.1985.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression analysis of electromyographic activity of masticatory muscles versus bite force

Abstract: – Electromyographic (EMG) activity of the superficial masseter and the anterior temporal muscles versus the bite force was studied in 10 young women. They were fully dentate and had no dysfunction of the stomatognathic system. The descending part of the trapezius muscle was also chosen for EMG registration. The average bite force between the first molars was 396 N (Newton). Steeper slopes for the EMG versus force regression curve at high contraction levels than at low contraction levels for the superficial mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 10 publications
0
45
1
3
Order By: Relevance
“…ings of the current study and some previous work. 11,18 The difference between the results in the current study and the findings of Mao and Osborn 20 may relate to the different methodologies used; a ramp force in the current study and incremental 50-N bite tasks in their study. Furthermore, neither van Eidjen et al 33 nor Mao and Osborn 20 investigated the first 50 N of bite force; the current study showed that many of the masseter SMUs were recruited in this part of the contraction.…”
Section: Variability In the Contribution Of Muscles To Jawcontrasting
confidence: 65%
“…ings of the current study and some previous work. 11,18 The difference between the results in the current study and the findings of Mao and Osborn 20 may relate to the different methodologies used; a ramp force in the current study and incremental 50-N bite tasks in their study. Furthermore, neither van Eidjen et al 33 nor Mao and Osborn 20 investigated the first 50 N of bite force; the current study showed that many of the masseter SMUs were recruited in this part of the contraction.…”
Section: Variability In the Contribution Of Muscles To Jawcontrasting
confidence: 65%
“…The descending and transverse portions of the muscle have been shown to be inactive during free movements of the head (Yamshon and Bierman, 1948;Freitas and Vitti, 1980;Bull et al 19841, but activity has been observed during neck extension (Schuldt, 1988). There is evidence suggesting a possible interplay between the jaw elevator muscles and the descending portion of the trapezius muscle (Hagberg et al, 1985;Valentino et al, 1987).…”
Section: Introductionmentioning
confidence: 97%
“…15 Whereas bite force measurements give information about the resulting force of all jaw-closing muscles, specific information on the contribution of the masseter and temporalis muscles can be obtained by surface electromyography (EMG). 2,8,13,18 To our knowledge, there have been no reports of studies in which maximal bite force or maximal masticatory muscle activity was quantified in patients with myasthenia gravis, in whom bulbar muscle weakness is well described. 4,10,16,20 The aim of the present study was to quantify masticatory muscle strength in terms of maximal effort in patients with myasthenia gravis and to compare the results with those of a control group (all subjects matched on an individual level).…”
mentioning
confidence: 99%